2008
DOI: 10.1016/j.expneurol.2007.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Administration of phosphodiesterase inhibitors and an adenosine A1 receptor antagonist induces phrenic nerve recovery in high cervical spinal cord injured rats

Abstract: High cervical spinal cord hemisection interrupts the descending respiratory drive from the medulla to the ipsilateral phrenic motoneurons, consequently leading to the paralysis of the ipsilateral hemidiaphragm. Previous studies have shown that chronic oral administration of theophylline, a phosphodiesterase inhibitor and an adenosine receptor antagonist, can restore function to the quiescent phrenic nerve and hemidiaphragm ipsilateral to hemisection. Both of these actions of theophylline result in an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…The results of this study have extended a previous study from our laboratory in which we reported that long-term (3-day) administration of phosphodiesterase inhibitors such as pentoxifylline and rolipram can bring about long-lasting phrenic nerve recovery in animals subjected to a left C2 spinal cord lesion (21). These studies provide support for the exploration of cAMPelevating agents as an effective approach in alleviating some of the respiratory insufficiency that is associated with high cervical spinal cord injury.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study have extended a previous study from our laboratory in which we reported that long-term (3-day) administration of phosphodiesterase inhibitors such as pentoxifylline and rolipram can bring about long-lasting phrenic nerve recovery in animals subjected to a left C2 spinal cord lesion (21). These studies provide support for the exploration of cAMPelevating agents as an effective approach in alleviating some of the respiratory insufficiency that is associated with high cervical spinal cord injury.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, we have shown that, after a left C2 spinal cord lesion, chronic inhibition of phosphodiesterase activity (over a 3-day period) can induce long-lasting phrenic nerve recovery in the previously quiescent left phrenic nerve (21). Furthermore, other studies have implicated the cAMP signaling cascade as a possible stimulator of respiratory neurons (22,23).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, intravenous rolipram restored respiratory-related activity to the phrenic nerve ipsilateral to the injury and significantly enhanced phrenic nerve inspiratory burst activity in both normal and C2 hemisected animals. These results provided evidence that PDE inhibitors can Science Publications AJN strengthen spared ineffective synaptic connections at the level of the phrenic nucleus and may enhance phrenic nerve output and restore respiratory related phrenic nerve function after high cervical SCI (Kajana and Goshgarian, 2008).…”
Section: Phosphodiesterase Inhibitors (Rolipram)mentioning
confidence: 76%
“…Kajana and Goshgarian (2008) shown that rolipram can increase phrenic nerve output ipsilateral to an experimental C2 hemisection lesion. Additionally, intravenous rolipram restored respiratory-related activity to the phrenic nerve ipsilateral to the injury and significantly enhanced phrenic nerve inspiratory burst activity in both normal and C2 hemisected animals.…”
Section: Phosphodiesterase Inhibitors (Rolipram)mentioning
confidence: 96%
“…The synthesis steps of the nanoconjugate are described in Figure 2a. MSA-capped AuNP was prepared according to the literature (Jana et al, 2001). The proform of DPCPX ( pro-DPCPX) was synthesized based on the Mannich reaction (Sloan and Bodor, 1982).…”
Section: Nanoconjugate Synthesismentioning
confidence: 99%